Donor lymphocyte infusions for chronic myeloid leukemia relapsing after allogeneic stem cell transplantation: may we predict graft-versus-leukemia without graft-versus-host disease? - Radujković, Aleksandar (Biology of blood and marrow transplantation, 2015)
Donor lymphocyte infusions (DLI) are an effective treatment for relapsed chronic myeloid leukemia (CML) after allogeneic stem cell transplantation (alloSCT). Leukemia resistance and secondary graft-versus-host disease (GVHD) are major obstacles to success with DLI. The aim of this study was to identify pre-DLI factors associated with prolonged survival in remission without secondary GVHD. We retrospectively analyzed 500 patients treated with DLI for CML relapse (16% molecular, 30% cytogenetic, and 54% hematological) after alloSCT. The overall probabilities of failure- and secondary GVHD-free survival (FGFS) were 29% and 27% at 5 and 10 years after DLI, respectively. The type of relapse was the major factor influencing FGFS (40% for molecular and/or cytogenetic relapse and 20% for hematological relapse at 5 years, P < .001). Chronic GVHD before DLI and an interval <1 year between alloSCT and first DLI were independently associated with inferior FGFS in patients with molecular and/or cytogenetic relapse. Consequently, FGFS was 13%, 35%, to 56% at 5 years in patients with 2, 1, and 0 adverse features, respectively. In patients with hematological relapse, independent adverse prognostic factors for FGFS were initial dose of CD3+ cells ≥ 50 × 106/kg, donor-recipient sex mismatch, and chronic GVHD before DLI. FGFS was 0%, 17%, 33%, to 37% in patients with 3, 2, 1, and 0 adverse features, respectively. The probability of survival in remission without secondary GVHD was highest (>50% at 5 years) when DLI were given beyond 1 year from alloSCT for molecular and/or cytogenetic CML relapse that was not preceded by chronic GVHD.